Гормональний статус жінок з гіперпролактинемією та непліддям - Склярова, В.О. (Таврический медико-биологический вестник, 2013)
В работе показано, что уровень пролактина у женщин с бесплодием может повышаться до 40-69 нг/мл, при этом у 22% пациенток выявлено нарушение менструального цикла, у 29% пациенток с вторичным бесплодием отмечены репродуктивные потери беременности, у 14% женщин с первичним бесплодием присутствовали признаки склерополикистозных яичников, у 60% женщин наблюдалась галакторея І-ІІІ степени, интенсивность которой не зависела от уровня пролактина в крови. У пациенток с гиперпролактинемией и бесплодием выраженных изменений концентрации ТТГ, ЛГ, ФСГ, свободного и общего тестостерона, кортизола, эстрадиола и антител (АТПО, АТТГ) в плазме крови не обнаружено. Соотношение ЛГ/ФСГ было выше 2,5 у 17% женщин, повышенное содержание кортизола на фоне гиперпролактинемии наблюдалось у 15% обследованных пациенток. It has been established that the level of prolactin in women with infertility may rise to 40-69 ng/ml; in 22% of patients irregular menstruation was revealed, in 29% of patients with secondary infertility reproductive losses of pregnancy were registered, 14% of women with primary infertility had signs of scleropolycystic ovaria, 60% of women had galactorea of the I-III degree, the intensity of which was not dependent on the level of prolactin in the blood. In patients with hyperprolactinemia and infertility, no pronounced changes in the concentration of TSH, LH, FSH, free and general testosterone, cortisol, estradiol, and antibodies (ATPO, ATTH) in plasma were found. The ratio of LH/FSH was above 2.5 in 17% of women, high levels of cortisol on the background of hyperprolactinemia was observed in 15% of the surveyed patients.